Placental Lesions in Meconium Aspiration Syndrome - Kim, Binnari (J Pathol Transl Med, 2017)
BACKGROUND: Meconium aspiration syndrome (MAS) is defined by respiratory distress requiring supplemental oxygen in a meconium-stained neonate. MAS is clinically subclassified as mild, moderate, and severe according to the oxygen requirement. The aims of this study were to compare the histological findings in the placentas of MAS neonates with those of meconium-stained but non-MAS neonates and to analyze the correlation between the severity of MAS and the grade of its histological parameters. METHODS: We collected 160 singleton term placentas from neonates with meconium staining at birth from a tertiary medical center, Seoul, Republic of Korea. We reviewed hematoxylin and eosin sections of tissue samples (full-thickness placental disc, chorioamniotic membranes, and umbilical cord). RESULTS: Funisitis was present more frequently in MAS than in non-MAS (p < .01), of which the stage was correlated with the severity of MAS (p < .001). The histological findings consistent with maternal underperfusion and chronic deciduitis were more frequent in MAS than in non-MAS (p < .05). There was a correlation between the degree of chorionic vascular muscle necrosis and the severity of MAS (p < .05). CONCLUSIONS: Our results suggest that fetal inflammatory response evidenced by funisitis occurs prenatally in MAS and that the stage of funisitis and of chorionic vascular muscle necrosis may be a predictive marker of the severity of MAS.